The Development Teaching Materials Subject Class Calculus of Many Variable Based on Discovery Learning Model at Education Faculty University of Muhammadiyah Sumatera Utara - Wahyuni, Sri; Bara, Ismail Hanif Batu; Dachi, Surya Wisada (International Journal for Educational and Vocational Studies, 2020)
This study is applied research. It is focus in development materials teaching course of calculus many variable basic on discovery learning model. In this research used developing 4D (define, design, develop, and disseminate). Destination research is for determine how to validity from development materials teaching course of calculus many variable basic on discovery learning model, and how to effectiveness in development of teaching material courses of calculus many variable basic on discovery learning model. The result of the research is teaching material courses of calculus many variable on discovery learning model. The result of research materials teaching course validated by experts. Result of validity is calculated with average for each indicator. Therefore effectiveness its calculate with means of  student response to materials teaching course. In this research result that materials teaching course is valid. Therefore, student response result is 94.45%, it means the effectiveness of teaching material course is very good.